Introduction to Gregorio Bermann's Mental Health in China - Franca Ongaro Basaglia (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
This text presents a translation of Franca Ongaro Basaglia's "Introduzione" to the Italian edition of Gregorio Bermann's book La salute mentale in Cina, published by Giulio Einaudi in 1972. Franca Ongaro was born in Venice in 1928. Upon completing her studies at a classical secondary school, she began to write children's literature. In 1953, she married Franco Basaglia and took his surname. The Gorizia psychiatric hospital impacted her interests and solidified her commitment to transforming the institutions and culture surrounding madness. She authored several essays with Franco Basaglia and other members of the group at Gorizia, and was a tireless researcher and feminist activist. Between 1983 and 1992, she was twice elected senator for the Independent Left, and from that position led a cultural and parliamentary crusade to enact the principles of psychiatric reform and authored the project to implement Law 180 - which had been passed by Parliament in 1978 - which set into motion the dismantling of Italy's psychiatric hospitals. Franca Ongaro Basaglia died in her Venice home on January 13, 2005.